Neuromodulation of the prefrontal cortex by iTBS: effects on the entrepreneurial attitude as evaluated by TAI test - Gomes, Pedro Miguel Vasconcelos (2022)
Introduction: Neuroentrepreneurship research suggests the importance in potential entrepreneurs of traits such as impulsiveness and novelty-seeking behaviour, along with an ambidextrous and flexible decision-making capacity that allows successful entrepreneurs to efficiently switch between exploitation behaviour (associated with regions involved in value-representation such as the ventromedial prefrontal cortex) and exploration behaviour (associated with attention- and cognitive-control frontoparietal regions). Simultaneously, the importance of creativity and ability for divergent thinking has also been underscored. The neurobiological basis for such functions is still being elucidated, but has pointed to the importance of several network-integrated prefrontal cortex regions involved in higher cognitive and attention-control mechanisms (such as the dorsolateral prefrontal cortex and frontopolar cortex) allowing the switching between exploitative and explorative behaviour, decision-making and relaxing of previous rules and constraints for innovative problem solving. Neuromodulation studies have shown changes in determinants of entrepreneurial attitude such as strategic decision-making, risk and novelty-seeking behaviour. In this exploratory study, we analysed the effects of stimulation of the right dorsolateral prefrontal cortex (DLPFC) on a test for entrepreneurial aptitude (TAI) in a group of 13 healthy volunteers randomly selected for either sham or active stimulation with intermittent theta burst stimulation (iTBS). Materials and methods: A total of 13 healthy volunteers were randomly allocated for either active (n=7) or sham (n=6) one-session iTBS stimulation of the right DLPFC. They were subsequently asked to answer the Entrepreneurial Attitude Test (TAI), which evaluates the determinants of entrepreneurial attitude in 8 factors and gives a global score, classified in three groups. Results: Mean TAI factor 3 scores (“adaptability”) were significantly higher in the active than in the sham group (6,64% ± 2,84%, p=0,039). Otherwise, there were no statistically significant differences in most TAI scores. Mean global TAI scores put the active group in the high-entrepreneurial attitude range (75,71%), and the sham group on the mid-entrepreneurial attitude range (71,66%), although such difference was not statistically significant (4,05% ± 2,67%, p=0,157). Discussion: Higher attention-control mechanisms (mediated by DLPFC via connections with the frontopolar and parietal cortices) which allow an efficient switching between exploration and exploitation behaviour may be a possible physiological basis for an ambidextrous entrepreneurial mindset, and thus the probable cause for the stimulated group having TAI factor 3 (“adaptability”) scores significantly higher than non-stimulated group. Despite stimulation of a major top-down cognitive control region of the prefrontal cortex, creativity’s neurobiology is increasingly understood in terms of the insertion of the relevant regions into major brain networks (such as default mode network or cognitive control network), such that modulation of other regions (such as the anterior temporal cortex) may be important for achieving improvements in creativity, innovativeness and insight problem solving, determinants for entrepreneurial behaviour. This, along our reduced sample size, possibly prevented us from finding other significant results in other entrepreneurship factors. Nevertheless, the fact that the active group had mean higher (although not significant) global TAI score, possibly suggests stimulation of the right DLPFC, if increasing activity of the higher-attention control mechanisms and stimulating some components of creativity (possibly divergent thinking and insight problem-solving), probably had indeed some overall effect in the determinants of entrepreneurial attitude, possibly worthy of future research. Conclusion: Stimulation of the higher cognitive and attention-control mechanisms (possibly the physiological basis for an ambidextrous entrepreneurial mindset) by stimulation of the right DLPFC is reflected in increased TAI factor 3 (“adaptability”) scores. The integration in future entrepreneurship neuromodulation protocols of open answer questionnaires or gambling tasks eventually allowing pre- and post-analysis is a suggestion to more directly evaluate creativity/innovativeness in future neuroentrepreneurship research.